2011
DOI: 10.1007/s10705-011-9478-5
|View full text |Cite
|
Sign up to set email alerts
|

Regional-scale phosphorus flows and budgets within France: The importance of agricultural production systems

Abstract: Large-scale studies at the regional, national and global scales are increasingly needed to assess nutrient flows in agroecoystems and to identify their drivers. In this study, we aimed to quantify the extent to which regional phosphorus (P) flows and soil P budget depend on agricultural production systems. Phosphorus was taken as a case study due to its sorbing properties in soil and to the many questions concerning its future availability. The issue was studied from two different stages: (1) for the 21 admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 44 publications
2
57
0
1
Order By: Relevance
“…The negative impacts of this perturbation on the natural environment depend on how much P is lost from regions with intensive fertilizer use (Smil, 2000;Bennett et al, 2001). P application differs significantly between countries and crop types (Grote et al, 2005), and previous researchers have attempted to estimate the P flows in agricultural systems in Europe (Ott & Rechberger, 2012), the United States (Suh & Yee, 2011), China (Ma et al, 2011), France (Senthilkumar et al, 2012), Australia (Cordell et al, 2013), and the world (Smil, 2000;Liu et al, 2008;MacDonald et al, 2011;Schipanski & Bennett, 2012). International trade and regional agricultural policies affect P budgets by increasing or decreasing the gap between P inputs and P outputs in agricultural land (Grote et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The negative impacts of this perturbation on the natural environment depend on how much P is lost from regions with intensive fertilizer use (Smil, 2000;Bennett et al, 2001). P application differs significantly between countries and crop types (Grote et al, 2005), and previous researchers have attempted to estimate the P flows in agricultural systems in Europe (Ott & Rechberger, 2012), the United States (Suh & Yee, 2011), China (Ma et al, 2011), France (Senthilkumar et al, 2012), Australia (Cordell et al, 2013), and the world (Smil, 2000;Liu et al, 2008;MacDonald et al, 2011;Schipanski & Bennett, 2012). International trade and regional agricultural policies affect P budgets by increasing or decreasing the gap between P inputs and P outputs in agricultural land (Grote et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Awareness of the P crisis has been highlighted in the last couple of years by many studies that have investigated P status and its consequences at different spatial and temporal scales. For example, it has been shown that P flux heterogeneity, observed at the national scale (Senthilkumar et al, 2012a) and regional scale (Senthilkumar et al, 2012b), is most often due to industrial and agricultural activities. Moreover, soil P content expresses certain heterogeneity even at the field level (Juang et al, 2002;Umali et al, 2012), leading to site-specific fertilization recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…In France the national average balance decreased from 17.5 in 1990 to 4.4 kg P/ha in 2006. However, in 2006 it ranged from 17 kg P/ha in Brittany, a region with a high livestock density, to 0 kg P/ha for the Central region with a low livestock density (Senthilkumar et al 2012).…”
Section: Characterization Of the P Budget In The Netherlandsmentioning
confidence: 99%
“…Senthilkumar et al 2012). However, when considering the importance of recycling it becomes relevant to include also the food and feed processing and consumption sector.…”
Section: Introductionmentioning
confidence: 99%